Unique Features of Subcortical Circuits in a Macaque Model of Congenital Blindness. (26th August 2019) - Magrou, Loïc; Barone, Pascal; Markov, Nikola T; Scheeren, Gwylan; Killackey, Herbert P; Giroud, Pascale; Berland, Michel; Knoblauch, Kenneth; Dehay, Colette; Kennedy, Henry
Abstract: There is an extensive modification of the functional organization of the brain in the congenital blind human, although there is little understanding of the structural underpinnings of these changes. The visual system of macaque has been extensively characterized both anatomically and functionally. We have taken advantage of this to examine the influence of congenital blindness in a macaque model of developmental anophthalmia. Developmental anophthalmia in macaque effectively removes the normal influence of the thalamus on cortical development leading to an induced "hybrid cortex (HC)" combining features of primary visual and extrastriate cortex. Here we show that retrograde tracers injected in early visual areas, including HC, reveal a drastic reduction of cortical projections of the reduced lateral geniculate nucleus. In addition, there is an important expansion of projections from the pulvinar complex to the HC, compared to the controls. These findings show that the functional consequences of congenital blindness need to be considered in terms of both modifications of the interareal cortical network and the ascending visual pathways.